Expanding the host cell ubiquitylation machinery targeting cytosolic Salmonella - Polajnar, Mira; Heilemann, Mike (EMBO reports, 2017)
Ubiquitylation is one of the cardinal post‐translational modifications in the cell, balancing several distinct biological processes and acting as a pathogen recognition receptor during bacterial pathogen invasion. A dense layer of polyubiquitin chains marks invading bacteria that gain access to the host cytosol for their selective clearance via xenophagy. However, the enzymes that mediate recognition of cytosolic bacteria and generate this ubiquitin (Ub) coat remain largely elusive. To address this, we employed an image‐based RNAi screening approach to monitor the loss of Ub on Salmonella upon depletion of human Ub E3 ligases in cells. Using this approach, we identified ARIH1 as one of the ligases involved in the formation of Ub coat on cytosolic bacteria. In addition, we provide evidence that the RING‐between‐RING ligase ARIH1, together with LRSAM1 and HOIP, forms part of a network of ligases that orchestrates recognition of intracellular Salmonella and participates in the activation of the host cell immune response.